A Dual Bi-directional Heuristic Development Framework - Murairwa, Stanley (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The research designs a multi-start heuristic framework. The heuristic development approachincreases the speed of convergence of heuristics to high quality optimum solutions. The multistartheuristic named the dual bi-directional (DBD) heuristic searches for the global optimumsolution in four concurrent directions with a pair search starting from both the beginning andending nodes. The search terminates when the four optimum tours connect to form an optimumround tour of all the search space nodes. Then, the DBD heuristic starts to improve the foundoptimum round tour in a unidirectional approach using a global search metaheuristic. The multistartheuristic framework decreases the non-convergence of the bi-directional approach byintroducing the unidirectional heuristic to improve the multi-start heuristic constructed optimumround tour. The development approach will allow the convergence of the bi-directional heuristic.